Bisbenzylisoquinoline alkaloids from Mahonia nepalensis - Mai, Nguyen Thi; Tuan, Tran Anh; Huong, Hoang Thanh; Minh, Chau Van; Ban, Ninh Khac; Kiem, Phan Van (Vietnam Journal of Chemistry, 2014)
From the wood of Mahonia nepalensis DC. 1821, two bisbenzylisoquinolines homoaromoline (1) and isotetrandrine (2) were isolated by using various chromatoghraphies. Their structures were characterized on the basis of the spectroscopic data (1D-NMR, HSQC, HMBC, ESI-MS) in comparison with the literature. This is the first report of 1 - 2 from Mahonia nepalensis. Keywords: Mahonia nepalensis, Isotetrandrine, Homoaromoline, Bisbenzylisoquinoline.